Let the Sadhus Talk: Ascetic Understanding of Hatha Yoga and Yogasanas - Bevilacqua, Daniela (Religions of South Asia, 2018)
Based on extensive interviews and ethnographic fieldwork, this article presents understandings of yoga among sadhus in northern India. Despite the existence of several ethnographic studies on Indian ascetic communities, very few have described their practices of yoga, nor the self-understanding of these communities regarding yoga in the wider religious life. This article bridges the gap between modern, transnational forms of yoga, philological research on textual yoga traditions, and the understanding of yoga within ascetic communities, by providing a cross-section of yoga practice across a range of ascetic orders. This article presents initial findings of what will be a five-year, full-time research project on ascetic practitioners of yoga, as part of the Hatha Yoga Project, SOAS, London.